A Robust PtNi Nanoframe/N‐Doped Graphene Aerogel Electrocatalyst with Both High Activity and Stability. (17th March 2021) - Yang, Jing; Hübner, René; Zhang, Jiangwei; Wan, Hao; Zheng, Yuanyuan; Wang, Honglei; Qi, Haoyuan; He, Lanqi; Li, Yi; Dubale, Amare Aregahegn; Sun, Yujing; Liu, Yuting; et al.
Abstract: Insufficient catalytic activity and stability and high cost are the barriers for Pt‐based electrocatalysts in wide practical applications. Herein, a hierarchically porous PtNi nanoframe/N‐doped graphene aerogel (PtNiNF‐NGA) electrocatalyst with outstanding performance toward methanol oxidation reaction (MOR) in acid electrolyte has been developed via facile tert‐butanol‐assisted structure reconfiguration. The ensemble of high‐alloying‐degree‐modulated electronic structure and correspondingly the optimum MOR reaction pathway, the structure superiorities of hierarchical porosity, thin edges, Pt‐rich corners, and the anchoring effect of the NGA, endow the PtNiNF‐NGA with both prominent electrocatalytic activity and stability. The mass and specific activity (1647 mA mgPt −1, 3.8 mA cm −2 ) of the PtNiNF‐NGA are 5.8 and 7.8 times higher than those of commercial Pt/C. It exhibits exceptional stability under a 5‐hour chronoamperometry test and 2200‐cycle cyclic voltammetry scanning. Abstract : PtNiNF‐NGA has PtNi nanoframes (PtNiNFs) with a high alloying degree, Pt‐rich corners and thin edges, anchoring effect of the N‐doped graphene aerogel to the PtNiNF, and hierarchical porosity. This endows it with fast mass transfer, enhanced intrinsic structure stability, modulated electronic state and optimized methanol oxidation reaction pathway, and thus both outstanding electrocatalytic activity and durability under acidic conditions.